Applications of the SR4G Transgenic Zebrafish Line for Biomonitoring of Stress-Disrupting Compounds: A Proof-of-Concept Study - Nozari, Amin; Do, Selena; Trudeau, Vance L. (Frontiers in Endocrinology, 2021)
Transgenic zebrafish models have been successfully used in biomonitoring and risk assessment studies of environmental pollutants, including xenoestrogens, pesticides, and heavy metals. We employed zebrafish larva (transgenic SR4G line) with a cortisol-inducible green fluorescence protein reporter (eGFP) as a model to detect stress responses upon exposure to compounds with environmental impact, including bisphenol A (BPA), vinclozolin (VIN), and fluoxetine (FLX). Cortisol, fluorescence signal, and mRNA levels of eGFP and 11 targeted genes were measured in a homogenized pool of 22-28 larvae, with six experimental replicates for each endpoint. Eleven targeted genes were selected according to their association with stress-axis and immediate early response class of genes. Dexamethasone (DEX) and hydrocortisone (CORT) were used as cortisol antagonist and agonist, respectively. All measurements were done in two unstressed and stressed condition using standardized net handling as the stressor. A significant positive linear correlation between cortisol levels and eGFP mRNA levels was observed (r2> 0.9). Based on eGFP mRNA levels in unstressed and stressed larvae two predictive models were trained (Random forest and Logistic regression). Both these models could correctly predict the blunted stress response upon exposure to BPA, VIN, FLX and the negative control, DEX. The negative predictive value (NPV) of these models were 100%. Similar NPV was observed when the predictive models trained based on the mRNA levels of the eleven assessed genes. Measurement of whole-body fluorescence intensity signal was not significant to detect blunted stress response. Our findings support the use of SR4G transgenic larvae as an in vivo biomonitoring model to screen chemicals for their stress-disrupting potentials. This is important because there is increasing evidence that brief exposures to environmental pollutants modify the stress response and critical coping behaviors for several generations.